POTENSI PEMANFAATAN DRONE UNTUK PENYEDIAAN DATA WILAYAH PESISIR - Bayu Prayudha (OSEANA, 2018)
POTENTIAL USE OF DRONE FOR PROVIDING DATA ON COASTAL AREA. The accurate data and information are needed for the decision maker to manage coastal area. However, the data and information of the coastal area are still lack because Indonesia has vast area and some of the locations are difficult to reach. Remote sensing is a technology that can be utilized to answer those needs. Some of the remote sensing data, especially satellite imagery can be freely acquired from various service providers using online media. Nevertheless, high resolution imagery data is still not available freely because it takes high cost and not always available at any time. One of the potential vehicle to acquire high resolution imagery data of coastal area is Unmanned Aircraft Vehicle (UAV) or widely known as drone.